Outdoor motivation moderates the effects of accessibility on mobility in old age - Kamin, Stefan; Beyer, Anja; Lang, Frieder (Zeitschrift für Gerontologie und Geriatrie, 2016)
Background: Mobility plays a major role in healthy aging and social participation. This study explored whether accessibility problems in the housing environment are negatively associated with mobility in old age and whether this association is moderated by differences in an individual's preference for spending time outside the home (outdoor motivation).   Material and methods: This article reports the results of a research project on mobility in  old age. The project included a survey study of 120 community-dwelling older adults between 59 and 92 years of age (mean = 71.7 years, SD = 7.3 years) living in the metropolitan region of Nuremberg, Germany. Objective assessments were conducted in the participants' housing environment to evaluate the magnitude of accessibility problems.   Results: Accessibility problems were negatively associated with mobility. Interaction analyses suggested a buffering effect of outdoor motivation on this association, i.e. participants who reported a preference for spending time outside the home had a higher mobility in the face of accessibility problems as compared with those who preferred staying at home.   Conclusion: Outdoor motivation may have protective effects for older adults when ac- cessibility problems challenge mobility. These findings contribute to improving the under- standing of how and under what circumstances older adults stay mobile and active in  everyday life. Considering interindividual differences in outdoor motivation may benefit interventions and public health programs that are aimed at enhancing mobility and social participation in old age.
Keywords: Housing Enaber; Motivation; Ecology of Aging; Mobility Limitations; Architectual Barriers